2015
DOI: 10.4172/2329-9126.1000206
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Cardiopulmonary Resuscitation and Associated Factors in Ethiopian University Medical Students

Abstract: Purpose: Cardiopulmonary resuscitation is a lifesaving procedure, performed to preserve patients' life until further management is going to follow. Having basic knowledge of CPR will be a crucial task of medical care providers. This study was done to evaluate knowledge, attitude, and practice and associated factors among clinical year medical students. Participants and Methods:Institutional based cross-sectional study was conducted to assess knowledge, attitude, practice and factors associated with cardiopulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 4 publications
(5 reference statements)
5
26
1
1
Order By: Relevance
“…In spite of this lack of knowledge and thus potential proficiency, attitudes towards CPR were generally positive. Similar knowledge deficiencies were reported among doctors and medical students in other LMICs, including South India [11], Sri Lanka [8], Jamaica [7], Nigeria [12], and Ethiopia [10].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In spite of this lack of knowledge and thus potential proficiency, attitudes towards CPR were generally positive. Similar knowledge deficiencies were reported among doctors and medical students in other LMICs, including South India [11], Sri Lanka [8], Jamaica [7], Nigeria [12], and Ethiopia [10].…”
Section: Discussionsupporting
confidence: 70%
“…Modifying previous literature, we created a semistructured questionnaire assessing adequate knowledge of CPR (based on the American Heart Association 2015 guidelines) in addition to attitudes towards CPR. The knowledge section contained 20 multiple-choice items that were previously used and validated in similar studies [4,9] while the attitude section included seven items also adapted from a previous study [10]. Knowledge questions were scored as binary variables; correct answers were given 1 point, while incorrect answers and "do not know" responses were given 0 points.…”
Section: Data Collection Toolmentioning
confidence: 99%
“…Inadequate level of BLS knowledge amongst nurses was found in studies conducted in United States of America (USA) [8], the United Kingdom (UK) [7], Finland [9] and Ireland [3]. Similar trend was also observed in countries like Bahrain [10], Greece [11], Nigeria [12] South Africa [13] and Ethiopia [14] but to our knowledge no previous study has been conducted in Eritrea to determine the effect of BLS training on the knowledge of nurses.…”
Section: Introductionsupporting
confidence: 71%
“…Lack of professional training of BLS was regarded as the most common hindering factor responsible for poor BLS knowledge by dental students. [18][19][20] Baduni N et al 21 reported score of 9.2 ±1.2 among dental practitioners which is better than the present study where mean score was 6.5. The majority of the study participants of the present study reported that BLS training should be a part of the dental curriculum and raised the point that there was no professional training available.…”
Section: IVcontrasting
confidence: 54%